2014
DOI: 10.1186/1745-6150-9-19
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteriophage-drived diversification of Mycobacterium abscessus

Abstract: BackgroundMycobacterium abscessus is an emerging opportunistic pathogen which diversity was acknowledged by the recent description of two subspecies accommodating M. abscessus, Mycobacterium bolletii and Mycobacterium massiliense isolates.ResultsHere, genome analysis found 1–8 prophage regions in 47/48 M. abscessus genomes ranging from small prophage-like elements to complete prophages. A total of 20,304 viral and phage proteins clustered into 853 orthologous groups. Phylogenomic and phylogenetic analyses base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 50 publications
(50 reference statements)
0
15
0
Order By: Relevance
“…The impact of the accessory genome on the evolution of the M. abscessus complex has been discussed by other researchers ( Choo et al, 2014 ; Sassi et al, 2014 ). In this analysis, we focused on the evolutionary pressure within the core genomes of the complex.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The impact of the accessory genome on the evolution of the M. abscessus complex has been discussed by other researchers ( Choo et al, 2014 ; Sassi et al, 2014 ). In this analysis, we focused on the evolutionary pressure within the core genomes of the complex.…”
Section: Discussionmentioning
confidence: 95%
“…Recombination, an important evolutionary force for the diversification of bacterial core genomes ( Ehrlich et al, 2005 ; Redfield et al, 2006 ), has been reported in the M. abscessus complex ( Sassi et al, 2014 ). Gene acquisition at the hypothetical common ancestor apparently played an important role in the evolution of this species complex and the enhanced virulence in some members could have come from their ability to acquire genes from different bacterial genera via horizontal transfer.…”
Section: Introductionmentioning
confidence: 99%
“…These prophages may play a major role in the evolution of STB, as previously reported for M . abscessus ( 27 ). Further study found that some STB isolates lacked the insertion element IS 1081, while a new ISMycA1 (GenBank accession number AJ619854) was discovered in the “ M. canettii ” CIPT140010059 genome ( 12 ).…”
Section: Particularities Of the Stb Organismsmentioning
confidence: 99%
“…Recently, the emergence of multidrug-resistant (MDR-TB) and extensively drug-resistant (XDR-TB) strains of M. tuberculosis has become a major global health concern (Cully M, 2014). The demand for new ways to overcome TB drug resistance has stimulated fresh research on mycobacteriophages and their lytic effi ciency against their hosts (Oldfi eld L M, et al, 2014;Sassi M, et al, 2014).…”
Section: Dear Editormentioning
confidence: 99%